Moderasi Beragama dalam Lembaga Dakwah: Perspektif Al-Washatiyah terhadap Dinamika Pemikiran Keagamaan - Alhaq, Dinda Luthfiaturrahmah; Firdaus, Muhammad; Yakub, M. (Ittishol: Jurnal Komunikasi dan Dakwah, 2025)
The purpose of this study is to understand the role of da'wah institutions in spreading the value of religious moderation in dealing with people with different backgrounds. In addition, how are the dynamics of religious thought in a moderate perspective and what are the relevance and implications of al-washatiyah thought for da'wah institutions. The research method used in this research is library research in this research is used to analyze and explore the concept of religious moderation in da'wah institutions with an al-washatiyah perspective through the study of relevant literature. The result of the research is that da'wah institutions since the time of the Prophet to the modern era have a strategic role in spreading Islamic teachings and forming a moderate society through various approaches that are adaptive to the context of the times. The dynamics of contemporary religious thought characterized by tensions between extremism and liberalism show the importance of applying the concept of al-washatiyah as a balanced, tolerant, and contextual middle way. The application of this principle in da'wah not only strengthens social cohesion and builds an inclusive society, but also changes the da'wah paradigm to be more educative, transformative, and responsive to global challenges. Thus, strengthening wasathiyah values in da'wah strategies is the key to realizing Islam as a religion of rahmatan lil 'alamin that is relevant and solutive in facing the dynamics of modern times. Penelitian ini bertujuan untuk mengeksplorasi peran lembaga dakwah dalam menyebarkan nilai-nilai moderasi beragama, mengelaborasi dinamika pemikiran keagamaan dalam perspektif moderat, serta menganalisis relevansi dan implikasi prinsip al-washatiyah terhadap arah dan pendekatan dakwah yang inklusif dan kontekstual. Metode penelitian yang digunakan dalam penelitian ini adalah library research. Data diperoleh dari literatur seperti buku, jurnal, artikel ilmiah, dan dokumen lembaga dakwah. Prosedur dilakukan melalui tiga tahap: identifikasi literatur, seleksi berdasarkan relevansi dan kualitas, serta analisis tematik guna menyusun sintesis konseptual yang mendalam dan kontekstual. Hasil penelitiannya moderasi dalam dakwah sangat penting, sebagaimana diungkapkan dalam QS. Al-Baqarah: 143, yang menyatakan umat Islam sebagai ummatan wasatan (umat pertengahan). Lembaga dakwah berperan dalam menanamkan enam prinsip utama: tawazun (keseimbangan), tasamuh (toleransi), i’tidal (keadilan), syura (musyawarah), i’tikad (keyakinan terbuka), dan rahmah (kasih sayang). Dinamika dalam pemikiran keagamaan menunjukkan perlunya pendekatan moderat. Pemikiran al-washatiyah menawarkan solusi dengan mendorong dakwah yang inklusif dan kontekstual, berfokus pada pembinaan umat. Dengan inovasi metode dakwah, peningkatan kapasitas da’i, dan kolaborasi lintas komunitas, lembaga dakwah dapat menciptakan citra Islam yang rahmatan lil‘alamin dan membentuk masyarakat yang toleran serta berdaya saing.